PERAN MEDIA MASSA NASIONAL DALAM POLITIK INTERNASIONAL - Prayetno Prayetno; Fahrysyah Aulya, Griyani Elisabeth Purba, Nasywa Yasmin Purba, Natasya Adriani, Rani Oktavia Purba, (ADISAM PUBLISHER, 2024)
National mass media plays an important role in international politics. In an era of advanced globalization, the mass media has the power to influence public opinion and shape perceptions of international politics. This article aims to present an abstract of the role of national mass media in international politics. The research is based on a literature study and content analysis of mass media related to international politics. In the context of international politics, the national mass media has several main roles. First, the mass media serve as communication channels between the government and the public. They convey information regarding foreign policy, diplomatic relations, and global issues to the public